THE IMPORTANCE OF USING TELECOMMUNICATION LEARNING PROJECTS IN INDEPENDENT EDUCATION - Azizov , Shavkat Abdurakhmanovich (Innovative Development in Educational Activities, 2023)
The article focuses on the importance and necessity of digitalization of independent education in the credit module system of higher education and the use of telecommunication educational projects. Information on the content, types and international projects of telecommunications educational projects is provided. The procedure for organizing project protection and its external evaluation criteria are explained.